2006
DOI: 10.1007/s00134-005-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Air ionisation and colonisation/infection with methicillin-resistant Staphylococcus aureus and Acinetobacter species in an intensive care unit

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 5 publications
0
28
2
2
Order By: Relevance
“…This value was much greater than those reported by Perdelli et al (2008) (1.8 cfu/plate) and Kerr et al (2006) (0-57 cfu, n = 30), but appeared to be an isolated case considering that the frequency of positive detection and the mean count were 9.65% and 1.64 cfu/plate, values which were less than those of P. aeruginosa and not markedly different than the others. Nonetheless, this result reflects the strong possibility to spread the bacteria though indirect pathways such as handling contaminated objects by the medical staff.…”
Section: Airborne and Surface-bound Bacteria Concentrations (Icu I)contrasting
confidence: 63%
See 1 more Smart Citation
“…This value was much greater than those reported by Perdelli et al (2008) (1.8 cfu/plate) and Kerr et al (2006) (0-57 cfu, n = 30), but appeared to be an isolated case considering that the frequency of positive detection and the mean count were 9.65% and 1.64 cfu/plate, values which were less than those of P. aeruginosa and not markedly different than the others. Nonetheless, this result reflects the strong possibility to spread the bacteria though indirect pathways such as handling contaminated objects by the medical staff.…”
Section: Airborne and Surface-bound Bacteria Concentrations (Icu I)contrasting
confidence: 63%
“…In a study by Kerr et al (2006) that compares the presence of MRSA and Acinetobacter spp. in the presence and absence of a negative air ionization in an ICU, they reported there was a significant reduction of the incidence of nosocomial Acinetobacter spp.…”
Section: Effects Of Patient Visitation Activities and Local Air Purifmentioning
confidence: 99%
“…Escombe et al (2009) showed that both UVGI and negative air ionisers reduced the transmission of TB from humans to guinea pigs in a clinical setting, while Kerr et al (2006) showed that the installation of ionisers in an ICU reduced the incidence of acinetobactor infections. Both trials had their challenges.…”
Section: Future Needsmentioning
confidence: 99%
“…Many electric appliances have negative-ion functions [9]. There is a great potential for utilization of NAI generators in preventing decay of fruits and vegetables [10], reducing the ambient air microbial load [11] and hospital-acquired infections in clinics [12,13] as well as preventing the spread of diseases in animal houses [14].…”
Section: Introductionmentioning
confidence: 99%